Proceedings of the 3rd International Conference on Green Environmental Engineering and Technology IConGEET 2021, Penang, Malaysia - Mohamed Noor, Norazian; Sam, Sung Ting.; Abdul Kadir, Aeslina; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents high-quality peer-reviewed papers from the 3rd International Conference on Green Environmental Engineering and Technology (IConGEET), held in July 2021, Penang, Malaysia. The contents are broadly divided into four parts: (1) air pollution and climate change, (2) environment and energy management, (3) environmental sustainability, and (4) water and wastewater. The major focus is to present current researches in the field of environmental engineering towards green and sustainable technologies. It includes papers based on original theoretical, practical, and experimental simulations, development, applications, measurements, and testing. Featuring the latest advances in the field, this book serves as a definitive reference resource for researchers, professors, and practitioners interested in exploring advanced techniques in the field of environmental engineering and technologies.
Appropriate Community-based Emergency Response Elements for Toxic Gas Release in Pasir Gudang, Johor -- Carbon Footprint Assessment from Purchased Electricity Consumption and Campus Commute in Universiti Malaysia Perlis (UniMAP): Pre- and During COVID19 Pandemic -- Changes of carbon in a hardwood forest by forecasts using a forest model -- Comparative Study of SO2 Removal Using Mesoporous Silica KCC-1 and SBA-15 -- Monsoonal Impact of the Precursors toward Tropospheric Nocturnal Ozone O3 (night-time ozone) during a Decadal Observation in Kuching, Sarawak, Malaysia -- Spatio-temporal Variation of Particulate Matter (PM10) during High Particulate Event (HPE) in Malaysia -- The influence of atmospheric stability on PM10 concentrations in urban areas.
Keywords: Environmental engineering; Civil engineering; Biotechnology; Bioremediation; Green chemistry; Environmental Civil Engineering; Environmental Engineering/Biotechnology.; Green Chemistry; Environmental engineering -- Congresses; Sustainable engineering -- Congresses